Influence of computers in students’ academic achievement - Simões, Sofia (2022)
Simões, S., Oliveira, T., & Nunes, C. (2022). Influence of computers in students’ academic achievement. Heliyon, 8(3), 1-13. [e09004]. https://doi.org/10.1016/j.heliyon.2022.e09004 ----------This work was supported by FCT (Fundação para a Ciência e a Tecnologia) under project DSAIPA/DS/0032/2018 (DS4AA).